Translocation of Tektin 3 to the equatorial segment of heads in bull spermatozoa exposed to dibutyryl cAMP and calyculin A. Issue 1 (27th December 2016) - Tsukamoto, Mariko; Hiyama, Erina; Hirotani, Karen; Gotoh, Takafumi; Inai, Tetsuichiro; Iida, Hiroshi
SUMMARY: Tektins (TEKTs) are filamentous proteins associated with microtubules in cilia, flagella, basal bodies, and centrioles. Five TEKTs (TEKT1, ‐2, ‐3, ‐4, and ‐5) have been identified as components of mammalian sperm flagella. We previously reported that TKET1 and ‐3 are also present in the heads of rodent spermatozoa. The present study clearly demonstrates that TEKT2 is present at the acrosome cap whereas TEKT3 resides just beneath the plasma membrane of the post‐acrosomal region of sperm heads in unactivated bull spermatozoa, and builds on the distributional differences of TEKT1, ‐2, and ‐3 on sperm heads. We also discovered that hyperactivation of bull spermatozoa by cell‐permeable cAMP and calyculin A, a protein phosphatase inhibitor, promoted translocation of TEKT3 from the post‐acrosomal region to the equatorial segment in sperm heads, and that TEKT3 accumulated at the equatorial segment is lost upon acrosome reaction. Thus, translocation of TEKT3 to the equatorial segment may be a capacitation‐ or hyperactivation‐associated phenomenon in bull spermatozoa. Mol. Reprod. Dev. 84: 30–43, 2017. © 2016 Wiley Periodicals, Inc .